Bir Mizah Gazetesi Akbaba'nın Gözünden Türkiye'de Demokrat Parti Yılları (1950-1960) - Konar, Elif (Fatih Sultan Mehmet Vakıf Üniversitesi, Lisansüstü Eğitim Enstitüsü, 2021)
Basın yayın faaliyetlerinin gelişim gösterdiği XX. yüzyılda gazete ve dergiler bu döneme ilişkin tarih araştırmalarında önemli kaynaklar olarak yerini almıştır. Ancak mizah yayınları için aynı şeyi söyleyebilmek pek mümkün değildir. Yayınlandıkları döneme yazı ve çizgileriyle ışık tutan mizah yayınları daha çok edebiyat, güzel sanatlar ve iletişim bilimleri bağlamında araştırılmıştır. Bu tezin amacı mizah yayıncılığının tarihi araştırmalara da kaynaklık yapabileceğini gösterebilmektir. Bu sebeple Cumhuriyet tarihinin en uzun ömürlü mizah dergilerinden olan Akbaba dergisinin 1952-1960 yılları arasında yayınlanmış olan koleksiyonu taranmış, tüm sayıları incelenmiştir. Giriş ve üç ana bölümden oluşan bu tezin ilk bölümünde mizahın toplumsal işlevi ve geçirdiği tarihsel evrim ile Türk kültürü ve toplumsal hayatında nasıl bir yer işgal ettiği anlatılmıştır. İkinci bölümde Akbaba dergisinin kuruluşundan tezin sınırları dahilinde 1960 yılına kadar takip ettiği yayın politikası, yazar ve çizer kadrosundan bahsedilmiştir. Tezin asıl konusunu oluşturan üçüncü bölüm de ise Akbaba dergisinde yer alan karikatürler ve mizahi yazılar merkeze alınarak derginin 1952-60 yılları arasında Türkiye‟de meydana gelen siyasi, ekonomik, sosyal ve kültürel gelişmelere bakışı ve bu olayları ne şekilde işlediği ele alınmıştır. Türkiye tarihi için önemli değiĢim ve dönüĢümlere sahne olan Demokrat Parti yılları bu çalıĢmada bir mizah dergisinin gözüyle yeniden değerlendirilmiĢtir. Böylece tarih mizah iliĢkisinin tarih araĢtırmalarına önemli katkılar sunabileceği gösterilmeye çalıĢılmıĢtır.

In the XX century, when press publishing activities developed, newspapers and magazines took their place as important sources in historical research related to this period. However, it is not possible to say the same thing for humor publications. Humor publications, which shed light on the period they were published with their writings and lines, were investigated more in the context of literature, fine arts and communication areas. The aim of this thesis is to show that humor publishing can also be a source for historical research. For this reason, the collection of Akbaba magazine, one of the longest-lasting humor magazines in the history of the Republic, published between 1952 and 1960 was scanned and all its issues were examined. In the first chapter of this thesis, which consists of the introduction and three main chapters, it is explained how humor occupies a place in Turkish culture and social life with its social function and historical evolution. In the second chapter, the publication policy, author and illustrating staff followed by Akbaba magazine until 1960 within the boundaries of the thesis are mentioned. The third chapter, which constitutes the main topic of the thesis, is centered on the cartoons and humorous articles in Akbaba magazine and discusses the magazine's view of the political, economic, social and cultural developments that occurred in Turkey between 1952-60 and how it handled these events. The years of the Democratic Party, which has undergone significant changes and transformations for The History of Turkey, were re-evaluated in this study through the eyes of a humor magazine. Thus, it was tried to show that the history humor relationship can make significant contributions to history research.
Democratic Party Years in Turkey Through the Eyes of a Newspaper Akbaba (1950-1960)
Keywords: Akbaba; Yusuf Ziya Ortaç; 1950-1960; Demokrat Parti; Adnan Menderes; Mizah; Democratic Party; Humor